Upaya Peningkatan Kinerja Dosen dalam Pengembangan Sumber Daya Manusia untuk Mendukung Visi dan Misi UPY - Siswanta, Lilik (Akmenika, 2013)
This research aimed to analyze the performance improvement effort Lecturer in Human Resource Development to support the Vision and Mission UPY The study population was all faculty PGRI University Yogyakarta some 114 people, with the use of saturated and representative sampling of respondents in Charge of human resources.Some efforts to make for human resources development in achieving the vision and mission of UPY, include: 1) explicitly implementing reward and punishment system, 2) developing human resource development based on Emotional and Spiritual Quotient Improvement, 3) providing the lecturers with more opportunities to imple-ment programs in their work units, 4) developing human resource through planning involving the lecturers, and 5) establishing cooperation with other universities in the development of Tri Dharma Perguruan Tinggi.